Work engagement, satisfaction, and commitment: a cross-cultural network analysis - Emad Shdaifat (Academia Mental Health and Well-Being, 2026)
Introduction: To investigate both common patterns and observed variations in the psychological network structure of organizational constructs, this study examines the consistency of work engagement across two samples and the pathways associated with organizational commitment. Materials and methods: Two independent samples of registered nurses from governmental hospitals in Saudi Arabia (n = 222) and Jordan (n = 215) completed assessments measuring work engagement, job satisfaction, organizational commitment, job performance, flourishing, and entitlement. Separate Gaussian Graphical Models were created for each sample. Network centrality indices and Network Comparison Tests were employed to evaluate structural invariance across the two samples. Results: Work engagement emerged as the most central construct within both networks. The strongest consistently observed association was between work engagement and job satisfaction. Network Comparison Tests revealed overall structural invariance; however, differences were observed: organizational commitment was more closely associated with work engagement in Saudi Arabia, whereas in Jordan, it was more strongly linked to job satisfaction. Furthermore, a negative relationship between flourishing and entitlement was observed only in the Jordanian context. Conclusions: This exploratory network analysis identifies both shared and sample-specific patterns in organizational psychology, positioning work engagement as a central, stable hub across both contexts. It further highlights distinct pathways for organizational commitment and well-being observed in the two samples. However, the cross-sectional design and reliance on self-report measures preclude causal inferences, and thus the findings should be interpreted as exploratory.